Disambiguierung deutschsprachiger Diskursmarker: Eine Pilot-Studie - Fabienne H. Baider; Henriette Gezundhajt (Linguistik Online, 2004)
Framed within Antoine Culioli's Enunciative Model of language, this article suggests a new analysis regarding the semantic properties of the suffix -esque and argues that this suffix refers to an alterity expressed within a typical property. Moreover this article reassesses earlier findings made about the suffix -esque, namely its low productivity in creation of neologisms and its apparent usage limited to literary and journalistic styles. The alleged constraint for all its bases to be referring to a human being is also reconsidered and our semantic analysis questions the value of "extreme" supposedly added by -esque to the nominal basis. Indeed, its usage in French shows that if this suffix is no longer typically associated to a nominal basis referring to the people of a country (see mauresque or arabesque), the human dimension associated to the nominal basis such as in la soldatesque, is not always found either (see TV-esque). Rather, this suffix seems to have lost its role as a simple identifier towards a referential domain as found in expressions such as une oeuvre molièresque which could be glossed over as "une oeuvre typique de Molière". This identification is most of the time linked to a laudatory or negative appreciation on the part of the enunciator, as found in examples such as gargantuesque. Besides, the contemporary dynamism of the -esque flexion enables the creation of neologisms. These neologisms are derived from proper nouns (mitterrandesque) or from acronyms (rmiesque) that do not exhibit standard properties. This begs the question of whether the value which seemed to be added to the composite [noun + esque] is determined by the suffix itself or whether it is partially connected to the atypical notional value of the root's semantic value.